ICAM1 blockade improves ischemic muscle reperfusion in diabetic mice - Ninon Foussard; Célia Bourguignon; Virginie Grouthier; Caroline Caradu; Candice Chapouly; Alain-Pierre Gadeau; Thierry Couffinhal; Marie-Ange Renault (Cardiovascular Diabetology)
Abstract Background Chronic Limb-Threatening Ischemia (CLTI) represents the most advanced stage of Peripheral Artery Disease (PAD) and is associated with dire prognosis, characterized by a substantial risk of limb amputation and diminished life expectancy. Despite significant advancements in therapeutic interventions, the underlying mechanisms precipitating the progression of PAD to CLTI remain elusive. Methods Considering diabetes is one of the main risk factors contributing to PAD exacerbation into CLTI, we compared hind limb ischemia recovery in HFD STZ vs. non-HFD STZ mice to identify new mechanisms responsible for the exacerbation of PAD. Results We used three different mouse models of diabetes and found that blood flow recovery in HFD STZ mice is altered only from day 14 post-surgery. Consistent with this kinetics, we found that angiogenesis and myogenesis which typically occur between day five and day 14 post-surgery are not impaired in mice in which diabetes was induced by a high fat diet and streptozotocin injections (HFD STZ mice). On the contrary, we found that capillary functionality e.i. acquisition of functional intercellular junctions and immune quiescence is impaired in HFD + STZ mice. Notably, 28 days after hind limb ischemia surgery, HFD + STZ mice display significantly increased capillary permeability to IgG and significantly increased levels of ICAM1. This was associated with an increased macrophage infiltration and an impaired myocyte differentiation. Importantly, we used ICAM1-blocking antibodies to demonstrate that increased ICAM1 expression in HFD + STZ mice decreases white blood cell circulation velocity within the microcirculation, which impairs its perfusion. Notably anti-ICAM1 therapy did diminish macrophage infiltration and oxidative stress but not myopathy suggesting that myopathy characterized by small myocytes expressing higher level of MYH2 could be responsible for microangiopathy. Conclusion ICAM1 expression by the microvasculature impairs ischemic muscle reperfusion in HFD + STZ mice. Importantly, the increase in blood flow between day 14 and day 90 post-HLI surgery is not associated with an increased capillary density but with an improved functionality of capillaries.